Sawit Karet dan Kakao Sebagai Ide Penciptaan Motif Batik Tulis - Maulidya Putri; Wahyu Tri Atmojo; Raden Burhan Surya Nata Diningrat (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This research aims to create batik tulis motifs with inspiration from three main plantation commodities in North Labuhanbatu Regency, North Sumatra, namely palm oil, rubber, and cocoa. These three plants are not only economically important, but also have philosophical values that can be raised as visual and cultural wealth in the form of batik motifs. The method used in the creation of the work consists of three stages, namely exploration, design, and realization. Exploration is done through literature study, direct observation, and visual documentation of the morphology of the three plants. The design stage involved the stilation and deformation of the plant forms into batik motif designs. Furthermore, the realization stage was carried out using the written batik technique using canting on mori cloth. The research resulted in 12 written batik works that combine elements of aesthetics, philosophy of life, and the locality value of the Labuhanbatu Utara community. This research is expected to enrich the repertoire of contemporary batik design while supporting cultural preservation and the development of local wisdom-based creative industries.